Environment-friendly oxygen isolation and fire extinguishing material based on CCS, and preparation method and application thereof
Patent Information
- Application Number
- CN202510353238.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-03-25
AI Technical Summary
[0004]目前,煤矿隔氧防灭火技术主要采用传统的隔氧材料,如膨胀剂、阻燃剂等,但这些材料存在一些缺陷,如隔氧效果不佳、易老化、难以应用于复杂的地质条件等
[0037]1. The environmentally friendly oxygen-barrier fire-extinguishing material based on CCS of this invention uses rationally selected raw materials. It employs a composite of spandex, polyester fiber, polypropylene fiber, and high-solids-content polyurethane to form a permeable and wear-resistant surface. The introduction of polyurethane significantly enhances the impermeability and flexibility of the sealing material. A waterproof sealing composite fabric is obtained by mixing polyester fiber and glass fiber and then treating it with Sympatex film. After Sympatex film treatment, the waterproof sealing composite fabric significantly improves the waterproof performance of the area where it meets the goaf. Traditional sealing materials mainly rely on cement and inorganic materials, which have low flexibility and toughness, are prone to deterioration in humid environments, and have poor tensile strength. This material, however, combines multiple high-performance fibers, enhancing its stability in harsh environments and reducing the frequency of material failures and maintenance. The waterproof sealing composite fabric ensures excellent waterproof performance, forming an effective protective system. The material's elasticity and toughness allow it to adapt to minor changes in the ground surface, maintaining good sealing performance and contributing to improved overall project safety and reliability. The mesh frame connecting the permeable and abrasion-resistant cover to the waterproof sealing composite fabric is made of polypropylene fiber or polyester fiber and modified loofah. The wire stakes generate good toughness and elasticity between the cementitious materials, and provide support and structural stability with the solid waste-based self-foaming carbon capture material filled in the middle, while enhancing the overall strength and durability of the material.
Smart Images

Figure CN120206926B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of coal mine fire prevention technology, specifically to an environmentally friendly oxygen-barrier fire extinguishing material based on CCS, its preparation method, and its application. Background Technology
[0002] With the continued growth of global reliance on coal resources, coal mining and utilization face increasingly severe environmental challenges, particularly the problems of goafs and surface fissures generated during the mining of shallow coal seams. The mining of shallow coal seams often creates surface cracks and goafs. These cracks not only affect surface stability but can also allow outside air to seep into the goafs, potentially leading to coal seam spontaneous combustion and fires. Furthermore, there is a risk of CO2 leakage from the goafs, which can impact the surrounding environment and threaten safe production in the coal mine. Against this backdrop, the development of a highly efficient oxygen-barrier fire-fighting material is of paramount importance.
[0003] In recent years, oxygen-barrier fire prevention and extinguishing materials based on solid waste utilization have gradually attracted attention. These materials not only possess excellent oxygen-barrier properties but also effectively seal surface fissures, preventing external air from entering the goaf and reducing the risk of spontaneous combustion. Simultaneously, these materials exhibit good environmental adaptability and economic viability, meeting the requirements of sustainable development. More importantly, if this oxygen-barrier fire prevention and extinguishing material can be combined with CCS (carbon dioxide capture and storage) technology, it can react with CO2 in the goaf to form stable compounds, thereby effectively absorbing and storing CO2 escaping from the goaf while blocking oxygen infiltration. This characteristic not only helps alleviate the pressure brought about by climate change but also helps improve the safety of coal mines. By combining solid waste-based oxygen-barrier fire prevention and extinguishing materials with CCS technology, a new type of coal mine oxygen-barrier fire prevention and extinguishing technology is formed, which can not only seal fissures and block oxygen but also capture and utilize CO2, achieving the dual effects of environmental protection and resource utilization.
[0004] Currently, coal mine oxygen-barrier fire prevention and extinguishing technologies mainly utilize traditional oxygen-barrier materials, such as expanding agents and flame retardants. However, these materials have several drawbacks, including poor oxygen-barrier performance, easy aging, and difficulty in application to complex geological conditions. Furthermore, traditional oxygen-barrier materials typically cannot effectively absorb CO2, making it difficult to solve the CO2 leakage problem in goaf areas. In addition, goaf areas in shallowly buried coal seams often have significant air leakage, leading to rapid CO2 leakage and increasing safety risks in coal mines. Therefore, developing an oxygen-barrier material that can effectively plug leaks and absorb CO2 is of great significance for improving coal mine safety and reducing environmental pollution. Summary of the Invention
[0005] To address the problems existing in the prior art, the purpose of this invention is to provide an environmentally friendly oxygen-barrier fire prevention and extinguishing material based on CCS (Carbon Dioxide Capture and Storage), as well as its preparation and application. This invention combines fire prevention and extinguishing technology with environmentally friendly oxygen-barrier materials and CCS technology, providing an innovative solution to the problems of sealing surface fissures, air leakage in goaf areas, and CO2 sequestration in shallow coal seams. The implementation of this technology will help improve coal mine safety, reduce environmental pollution, and promote the sustainable development of the coal industry.
[0006] To achieve the above objectives, on the one hand, the present invention provides a method for preparing an environmentally friendly oxygen-barrier fire-extinguishing material based on CCS, comprising the following steps:
[0007] Step 1), material prefabrication;
[0008] ⑤ Prefabricated permeable and wear-resistant cover
[0009] A fabric is formed by blending spandex, polyester fiber and polypropylene fiber, and then polyurethane is coated on the surface of the fabric and cured to obtain a water-permeable and wear-resistant cover.
[0010] ⑥ Prefabricated waterproof and sealing composite fabric
[0011] Glass fibers with a diameter of 9-13μm and aramid fibers with a diameter of 12-15μm are immersed in a polyurethane adhesive solution, then removed and dried and cured. The treated glass fibers and aramid fibers are laid on both sides of a Sympatex film with a thickness of 10-20μm, and then hot-pressed to obtain a waterproof and sealing composite fabric with a three-layer structure.
[0012] ⑦ Prefabricated solid waste-based self-foaming carbon capture material
[0013] Steel slag, blast furnace slag, fly ash, desulfurized gypsum, modified starch-based foaming agent, cocoamide, xanthan gum and water are mixed evenly to obtain solid waste-based self-foaming carbon capture material, wherein the modified starch-based foaming agent is obtained by combining corn starch and water glass;
[0014] ⑧ Prefabricated mesh support
[0015] Loofah sponges are broken into segments of 1–5 cm in size and soaked in a mixed aqueous solution of chloropolyvinylidene emulsion and VAE emulsion to modify the loofah sponges and obtain modified loofah sponge fibers. Then, the temperature of the hot press is controlled at 100–150°C and a pressure of 1–5 MPa is applied for hot pressing to melt-bond the thermoplastic polyurethane material with the modified loofah sponge fibers and polypropylene / polyester fibers to form a multilayer structure and obtain a mesh scaffold.
[0016] Step 2), composite assembly of prefabricated materials;
[0017] First, a waterproof and sealing composite fabric is laid as the bottom surface. The mesh support is then evenly spaced on the waterproof and sealing composite fabric and fixed with adhesive. Next, solid waste-based self-foaming carbon capture material is filled into the frame formed by the mesh support, so that it is evenly filled into the entire space of the mesh support. Finally, a water-permeable and wear-resistant cover is laid as the top surface and fixed to the mesh support with adhesive, thus obtaining an environmentally friendly oxygen-barrier fire-extinguishing material based on CCS.
[0018] As a further preferred technical solution of the present invention, the raw materials of the permeable and wear-resistant cover are: textile waste spandex accounting for 10-15 wt%, polyester fiber accounting for 40-55 wt%, and polypropylene fiber accounting for 30-50 wt%; the coating amount of polyurethane accounts for 10-14% of the total fiber mass. Specifically, spandex is blended with polyester fiber and polypropylene fiber in a certain proportion, and polyurethane is uniformly coated onto the fabric by roller coating. The coated material is then naturally cured at room temperature for 24 hours to allow the polyurethane coating to initially cure. The cured material is then placed in an oven and dried at 60-80℃ for 2-4 hours to ensure complete curing of the coating.
[0019] As a further preferred technical solution of the present invention, the aramid fiber accounts for 45%-55% of the mass of the fiber raw materials used in the waterproof sealing composite fabric, and the glass fiber accounts for 55%-45% of the mass.
[0020] As a further preferred embodiment of the present invention, after the glass fiber and aramid fiber are respectively immersed in a polyurethane adhesive solution, the fibers are removed and cured, preferably by natural drying for 24 hours to ensure full penetration of the polyurethane adhesive. Then, the treated glass fiber, Sympatex film, and treated aramid fiber are stacked sequentially and subjected to hot pressing. The preferred hot pressing process is to use a hot pressing device to press at 120-150°C and 10-15MPa for 5-10 minutes to effectively bond the layers together, forming a whole waterproof and sealing composite fabric.
[0021] As a further preferred technical solution of the present invention, the raw material components of the solid waste-based self-foaming carbon capture material are prepared according to the following weight: 30-40 parts steel slag, 25-35 parts blast furnace slag, 15-25 parts fly ash, and 5-10 parts desulfurized gypsum; the modified starch-based foaming agent and coconut oil amide account for 3%-5% of the total mass of the solid waste-based self-foaming carbon capture material; the mass ratio of the modified starch-based foaming agent to coconut oil amide is 4:1, and the modified starch-based foaming agent is prepared from corn starch and water glass at a mass ratio of 1:0.3; the amount of xanthan gum is 0.1%-0.3% of the total mass of the modified starch-based foaming agent and coconut oil amide; and the water-to-solid ratio is 0.4-0.5.
[0022] As a further preferred technical solution of the present invention, the mesh support is composed of 35-45% modified loofah fiber and 55-65% polypropylene / polyester fiber by mass ratio, which are melt-bonded by adding 15% thermoplastic polyurethane.
[0023] According to another aspect of the present invention, the present invention also provides an environmentally friendly oxygen-barrier fire extinguishing material based on CCS, which is prepared by the above-described method.
[0024] According to another aspect of the present invention, the present invention also provides an application of CCS-based environmentally friendly oxygen-barrier fire prevention and extinguishing material for the prevention and control of spontaneous combustion of coal in goaf areas of shallow buried coal seams, comprising: unfolding the environmentally friendly oxygen-barrier fire prevention and extinguishing material and completely covering the surface fissures of the shallow buried coal seam; and then injecting water into the environmentally friendly oxygen-barrier fire prevention and extinguishing material so that the solid waste-based self-foaming carbon capture material naturally foams and solidifies inside the structure of the mesh support.
[0025] The following is a method for applying CCS-based environmentally friendly oxygen-barrier fire prevention and extinguishing materials to coal mines for oxygen-barrier fire prevention and extinguishing:
[0026] S1: On-site assessment and investigation
[0027] Before sealing surface fissures and sequestering CO2 in shallow coal seams, an environmental impact assessment of the leaking areas is conducted to ensure no negative impact on the surrounding ecosystem. Then, a detailed investigation and assessment of the corresponding goaf and surface fissures is carried out to determine the depth, width, and distribution of the fissures, providing a basis for subsequent filling schemes. Based on the survey results, the specific locations where oxygen-barrier materials need to be filled are determined.
[0028] S2: Preparation and on-site surface treatment of environmentally friendly oxygen-barrier fire extinguishing materials based on CCS.
[0029] Based on the size and coverage area of the fissures at the site, confirm the specifications of the oxygen barrier material and prepare the necessary construction tools. Before laying the oxygen barrier material, check the surface humidity; if it is too damp, wait for the surface to dry naturally. Simultaneously, before sealing the surface cracks in the shallowly buried coal seam surface fissure leakage areas after exploration, clean and treat the surrounding surface of the sealing area to ensure good adhesion of the environmentally friendly oxygen barrier material. After cleaning, ensure the surface is dry and free of impurities. For larger or obvious fissures, use concrete filling material to seal them to enhance the adhesion of the oxygen barrier material.
[0030] S3: Laying and fixing of environmentally friendly oxygen-barrier fire-extinguishing materials based on CCS
[0031] Based on the preliminary survey and assessment results, the environmentally friendly oxygen-barrier material was laid flat in the designated area, ensuring sufficient coverage and close bonding with the surrounding soil. It was then secured to the ground using mechanical fixing devices (such as nails and screws) to prevent displacement. Water was then injected into the oxygen-barrier material several times to allow the solid waste-based self-foaming carbon capture material to naturally foam and solidify within the linear pile structure. The water injection interval was maintained at 3 hours per injection, with 8-10 injections in total. For larger cracks, overlapping may be necessary to ensure the material forms a complete oxygen barrier, preventing oxygen penetration.
[0032] S4: CO2 Injection and Sequestration
[0033] CO2 captured by coal-fired power plants in mining areas is transported through boreholes or pipelines to the goaf areas below the sealed surface fissures. The sealed goaf and the surface can form a closed space to store CO2. At the same time, the oxygen-barrier material can also absorb and block CO2 from escaping from the goaf to the air leakage channels, thereby achieving multiple effects such as pollution reduction and carbon reduction, inertization of the spontaneous combustion environment of coal in the goaf.
[0034] S5: Establishment of the monitoring system
[0035] The effectiveness of the oxygen barrier is ensured by real-time monitoring of parameters such as oxygen concentration, temperature, and pressure in the goaf area using sensors. The environmentally friendly oxygen barrier material is regularly inspected to assess its structural integrity and oxygen barrier effect; any defects are promptly addressed by replenishing or maintaining the material. If excessively high temperatures or oxygen concentrations are detected in the goaf, an emergency response procedure should be initiated immediately to ensure safety. The rapid-response capability of the oxygen barrier material should be utilized for further localized isolation to slow the rate of coal oxidation and temperature rise.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1. The environmentally friendly oxygen-barrier fire-extinguishing material based on CCS of this invention uses rationally selected raw materials. It employs a composite of spandex, polyester fiber, polypropylene fiber, and high-solids-content polyurethane to form a permeable and wear-resistant surface. The introduction of polyurethane significantly enhances the impermeability and flexibility of the sealing material. A waterproof sealing composite fabric is obtained by mixing polyester fiber and glass fiber and then treating it with Sympatex film. After Sympatex film treatment, the waterproof sealing composite fabric significantly improves the waterproof performance of the area where it meets the goaf. Traditional sealing materials mainly rely on cement and inorganic materials, which have low flexibility and toughness, are prone to deterioration in humid environments, and have poor tensile strength. This material, however, combines multiple high-performance fibers, enhancing its stability in harsh environments and reducing the frequency of material failures and maintenance. The waterproof sealing composite fabric ensures excellent waterproof performance, forming an effective protective system. The material's elasticity and toughness allow it to adapt to minor changes in the ground surface, maintaining good sealing performance and contributing to improved overall project safety and reliability. The mesh frame connecting the permeable and abrasion-resistant cover to the waterproof sealing composite fabric is made of polypropylene fiber or polyester fiber and modified loofah. The wire stakes generate good toughness and elasticity between the cementitious materials, and provide support and structural stability with the solid waste-based self-foaming carbon capture material filled in the middle, while enhancing the overall strength and durability of the material.
[0038] 2. In the CCS-based environmentally friendly oxygen-barrier fire-extinguishing material of this invention, the connection between the two layers of fabric and the function of the intermediate filling material form a high-toughness, waterproof, and structurally stable leak-stopping system. The overall frame structure has a certain degree of deformability, forming a multi-layered protective barrier capable of supporting the solid waste-based self-foaming carbon capture material. This design effectively disperses pressure, reduces local stress concentration, and creates a good sealed environment, further enhancing the oxygen-barrier fire-extinguishing effect. Furthermore, the stake frame provides structural support, allowing the upper and lower fabric layers to maintain a certain distance, thus forming a stable air layer and enhancing the oxygen-barrier effect. Simultaneously, the frame also promotes the uniform distribution of the intermediate self-foaming carbon capture material, ensuring good contact between it and the two fabric layers and improving carbon capture efficiency.
[0039] 3. In the CCS-based environmentally friendly oxygen-barrier fire-extinguishing material of this invention, the solid waste-based self-foaming carbon capture material preferably uses four types of solid waste—steel slag, blast furnace slag, fly ash, and desulfurized gypsum—as base materials. Various clinker materials are combined with modified starch-based foaming agents and additives to design a composite material integrating functions such as comprehensive utilization of solid waste, CO2 capture and mineralization storage, and oxygen-barrier fire extinguishing through foaming and gelling materials. Firstly, the selection of the four solid wastes demonstrates complementary components, mutually promoting hydration reactions, strength characteristics, impermeability and durability, environmental friendliness, and sustainability during the hydration process. These characteristics are specifically manifested in the following ways: steel slag has high alkalinity and activity, and can react with water to form hydrated silicates and hydrated aluminates, providing early strength; blast furnace slag can react slowly in water, providing long-term strength and durability; when the two are combined, they can provide abundant silicates, which helps to form hydraulic cementitious materials, and the early strength and later strength can be synergistically improved; and fly ash, as an active mineral admixture, can react with calcium-based oxides in steel slag and blast furnace slag to form hydrated calcium silicate (CSH), further improving the strength and durability of the hardened body. In addition, in the hydration reaction, desulfurized gypsum can also play a role in adjusting the pH value and improving the effectiveness of the reaction. The gypsum hydrate formed by it and CSH gel grow and interweave to form a dense network structure. Meanwhile, the solid waste-based material contains a large amount of alkaline components such as calcium and magnesium, which can react chemically with CO2 to convert CO2 into stable carbonate minerals. At the same time, the self-foaming process increases the specific surface area and porosity of the oxygen barrier material, providing more reaction interfaces for CO2 to contact with alkaline components. Therefore, the raw materials in the self-foaming carbon capture material of the present invention can produce excellent effects on sealing air leakage and capturing CO2 in shallow coal seam goaf areas.
[0040] 4. In the application of the CCS-based environmentally friendly oxygen-barrier fire extinguishing material of this invention, through multiple water injection processes, the synergistic hydration reaction of the four solid wastes not only releases heat and accelerates the solidification of the material, but also generates cementing materials such as calcium silicate hydrates, enhancing the strength and stability of the final product. Furthermore, the combination of solid wastes with modified starch-based foaming agent and coconut oil amide not only enhances the material's self-foaming performance, forming numerous pore structures, but also improves the material's flexibility and resistance to deformation, helping it adapt to the constantly changing geological morphology of shallow coal seams. Moreover, due to the material's porous structure, a large amount of CO2 can be captured and gradually mineralized within the material, enhancing its continuous capture capacity. Simultaneously, the reaction mechanism of modified starch and coconut oil amide does not involve acid-base reactions or thermal reactions that release CO2; therefore, no CO2 is generated during foam formation, ensuring the environmental friendliness of the foaming agent. In addition, multiple water injections increase the contact opportunities between CO2 and the solid waste material, enhancing the CO2 mineralization efficiency. As the hydration process proceeds, CO2 is gradually captured and converted into minerals. This gradual conversion process helps to improve the stability of the mineralization reaction and facilitates the long-term sequestration of CO2 leaked from the goaf.
[0041] 5. In the application of the CCS-based environmentally friendly oxygen-barrier fire-extinguishing material of this invention, the self-foaming carbon capture material, combined with two layers of fabric material and an intermediate mesh frame, forms a lightweight, porous, integrated oxygen-barrier fire-extinguishing and carbon emission reduction technology. This not only reduces the material's density but also improves its heat insulation and oxygen-barrier properties, enhancing its fire-resistant effect. On one hand, the oxygen-barrier material seals air-leaking fissures, controlling the flow of oxygen between the goaf and surface fissures, forming an oxygen barrier to prevent external oxygen infiltration. On the other hand, during mining, sealing fissures creates a closed underground space, allowing CO2 captured by the coal-fired power plant in the mining area to be introduced into the sealed underground space through pipelines or boreholes, forming a geological sequestration of CO2. Simultaneously, the solid waste-based self-foaming carbon capture material in the environmentally friendly oxygen-barrier material converts CO2 escaping upwards from the goaf into solid minerals (such as calcium carbonate), further enhancing the strength and sealing of the oxygen-barrier material. The combination of environmentally friendly oxygen-barrier materials and CCS (Computer-Based Separation) technology for coal mine fire prevention and extinguishing can effectively reduce the risk of fire in coal mines and improve mine safety. Simultaneously, the development and application of solid waste-based materials realizes resource recycling, aligning with the concept of sustainable development. Combined with CCS technology, it can accelerate CO2 mineralization and sequestration in coal mining areas, reducing greenhouse gas emissions and having a positive impact on environmental protection.
[0042] 6. The CCS-based environmentally friendly oxygen-barrier fire-extinguishing material of this invention is applicable to different types of coal mines, especially shallow-buried coal seam groups with surface fissures and air leakage, effectively reducing safety hazards under their special mining conditions. From the perspective of solid waste utilization, this technology is based on all solid waste materials such as steel slag, blast furnace slag, fly ash, and desulfurization gypsum, which not only realizes the recycling of waste but also reduces the demand for new materials, thereby reducing resource consumption and environmental pollution. From the perspective of carbon emission reduction, on the one hand, the self-foaming carbon capture material prepared in the oxygen-barrier material can absorb CO2 generated by spontaneous combustion in the goaf; on the other hand, by sealing the surface fissures and air leakage of the oxygen-barrier material and injecting CO2 into the closed space formed by the goaf, long-term carbon reduction is achieved, forming a continuous low-oxygen environment, improving the safety and stability of the mine, and reducing the risk of fire and explosion. In summary, this fire prevention and extinguishing technology integrates multiple technologies such as oxygen isolation, fire prevention, carbon reduction, and solid waste utilization to form a complete system solution, maximizing resource utilization and promoting the integrated utilization of solid waste and CO2. It has higher comprehensive application value than existing technologies.
[0043] 7. The preparation and application method of the CCS-based environmentally friendly oxygen-barrier fire prevention and extinguishing material of the present invention embodies the integrated innovation of multiple technologies, including efficient utilization of solid waste, improvement of material performance, prevention and control of goaf disasters, and mineralization and sequestration of CO2. The application of oxygen-barrier material and geological sequestration of CO2 can effectively reduce air leakage and prevent spontaneous combustion of coal in goaf. In addition, the efficient application of solid waste material and the mineralization and sequestration of CO2 can provide new ideas and directions for the coal mining industry to solve the problems of global climate change and resource shortage.
[0044] 8. The preparation and application method of the CCS-based environmentally friendly oxygen-barrier fire-extinguishing material of this invention, when used to isolate oxygen from surface fissures in shallow coal seams, can better adapt to complex terrain and fissure morphology. The operation is simple and the steps are clear, effectively isolating oxygen, preventing coal mine fires, and achieving CO2 capture and mineralization. The implementation and application of this technology not only reduces the risk of coal mine fires but also promotes the recycling of solid waste, reflecting the environmental protection and sustainable development concepts of modern mining. Attached Figure Description
[0045] The present invention will now be described in further detail with reference to the accompanying drawings and specific embodiments.
[0046] Figure 1 This is a schematic diagram of the structure of the solid waste-based high-toughness material of the present invention.
[0047] Figure 2 This is a schematic diagram of the solid waste-based high-toughness material of the present invention used for oxygen isolation in surface fissures of shallow buried coal seams.
[0048] In the figure: 1. Water-permeable and wear-resistant cover, 2. Waterproof and sealing composite fabric, 3. Solid waste-based self-foaming carbon capture material, 4. Mesh support, 100. Solid waste-based high-toughness material.
[0049] The objectives, features, and advantages of this invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0050] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0051] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art to which this invention pertains. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.
[0052] Example 1:
[0053] like Figure 1 As shown, an environmentally friendly oxygen-barrier fire-fighting material based on CCS (carbon dioxide capture and storage) includes a water-permeable and wear-resistant cover 1, a solid waste-based self-foaming carbon capture material 3, a waterproof and sealing composite fabric 2, and a mesh support 4. The water-permeable and wear-resistant cover 1 and the waterproof and sealing composite fabric 2 are laid flat and opposite to each other. The mesh support 4 has a three-dimensional mesh structure and serves as a support frame, evenly distributed and connected between the water-permeable and wear-resistant cover 1 and the waterproof and sealing composite fabric 2. The solid waste-based self-foaming carbon capture material 3 is filled within the structure of the mesh support 4 between the water-permeable and wear-resistant cover 1 and the waterproof and sealing composite fabric 2, thus forming a three-layer composite structure.
[0054] The permeable and wear-resistant cover, solid waste-based self-foaming carbon capture material, waterproof sealing composite fabric, and mesh support are prefabricated using the following methods:
[0055] The permeable and abrasion-resistant cover is made by blending 10% wt spandex, 40% wt polyester fiber, and 55% wt polypropylene fiber to form a fabric, and then coating the fabric with a polyester coating accounting for 15% of the total fiber weight. The specific preparation method is as follows: spandex, polyester fiber, and polypropylene fiber are blended in a certain proportion, and then the polyurethane coating is evenly applied to the fabric by roller coating. The coated material is naturally cured at room temperature for 24 hours to allow the polyurethane coating to initially cure. The cured material is then placed in an oven and dried at 80℃ for 2 hours to ensure complete curing of the coating, resulting in the permeable and abrasion-resistant cover for later use.
[0056] The solid waste-based self-foaming carbon capture material is composed of 40 parts steel slag, 30 parts blast furnace slag, 20 parts fly ash, and 10 parts desulfurization gypsum, with a water-to-solid ratio of 0.5. It also includes 4% by weight of modified starch-based foaming agent and coconut oil amide (mass ratio of modified starch-based foaming agent to coconut oil amide is 4:1), and 0.2% by weight of xanthan gum, which is the total mass of the modified starch-based foaming agent and coconut oil amide. The modified starch-based foaming agent is mainly prepared by combining corn starch and water glass in a mass ratio of 1:0.3. The corn starch is first dissolved in water, and then the water glass is added and thoroughly mixed.
[0057] The waterproof and sealing composite fabric is made of 45% aramid fiber and 55% glass fiber, treated with Sympatex film and water-based polyurethane adhesive. The specific preparation method is as follows: Glass fiber and aramid fiber are immersed separately in a polyurethane adhesive solution, allowing the polyurethane adhesive to fully penetrate the fiber surface and form a preliminary bond. After immersion, the fibers are removed and cured, and the polyurethane adhesive is cured by natural drying for 24 hours to ensure full penetration. The treated glass fiber, Sympatex film, and treated aramid fiber are then stacked sequentially, and finally hot-pressed at 130℃ and 12MPa for 6 minutes to effectively bond the layers, forming a complete waterproof and sealing composite fabric.
[0058] The mesh scaffold is made of 55% polypropylene fiber and 45% modified loofah sponge. The specific preparation method is as follows: the loofah sponge is broken into segments, with a size controlled between 1 and 5 cm. These segments are then soaked in a mixed aqueous solution of chloropolyvinylidene emulsion and VAE emulsion (volume ratio 1:1), and then removed for hot pressing. The hot press temperature is controlled at 120℃, and a pressure of 2 MPa is applied for compression for 15 minutes. During the hot pressing process, thermoplastic polyurethane material is simultaneously compounded with modified loofah sponge fiber and polypropylene fiber to form a multi-layer structure, thus obtaining a mesh scaffold with good mechanical properties, thermal stability, and aging resistance.
[0059] This embodiment also provides a method for preparing a CCS-based environmentally friendly oxygen-barrier fire extinguishing material, and a method for applying this CCS-based environmentally friendly oxygen-barrier fire extinguishing material to oxygen-barrier applications in surface fissures of shallowly buried coal seams, as detailed below:
[0060] 1) Based on the above-mentioned prefabricated materials, lay the waterproof sealing composite fabric, ensuring it is flat and wrinkle-free. Apply acrylic adhesive and evenly space the intermediate mesh supports, ensuring they are firmly fixed to the waterproof sealing composite fabric. After the waterproof sealing composite fabric and the intermediate mesh supports are in place, fill the solid waste-based self-foaming carbon capture material, evenly filling the entire space of the mesh supports with the mixed cementitious material, ensuring density. After the cementitious material is filled, lay the permeable and wear-resistant cover and fix it to the mesh supports with acrylic adhesive, thus obtaining the environmentally friendly oxygen-barrier fire-extinguishing material. Finally, roll up the fixed oxygen-barrier material and package it for later use.
[0061] 2) Environmentally friendly oxygen-barrier fire-fighting materials are used for sealing surface fissures in shallowly buried coal seams (e.g., Figure 2 ):
[0062] First, before sealing surface fissures and sequestering CO2 in shallow-buried coal seams, the environmental impact of the leaking areas is assessed to ensure no negative impact on the surrounding ecosystem. Then, a detailed investigation and assessment of the corresponding goaf and surface fissures is conducted to determine their depth, width, and distribution, providing a basis for subsequent filling plans. Based on the survey results, the specific locations where oxygen-barrier materials need to be filled are determined.
[0063] Secondly, based on the size and coverage area of the cracks at the site, confirm the specifications of the oxygen barrier material and prepare the necessary construction tools. Before laying the oxygen barrier material, check the surface humidity; if it is too damp, wait for the surface to dry naturally. Simultaneously, before sealing the surface cracks in the shallowly buried coal seam surface fissures and air leakage areas after exploration, clean and treat the surrounding surface of the sealing area to ensure good adhesion of the environmentally friendly oxygen barrier material. After cleaning, ensure the surface is dry and free of impurities. For larger or obvious cracks, use concrete filling material to seal them to enhance the adhesion of the oxygen barrier material.
[0064] Then, based on the preliminary survey and assessment results, the environmentally friendly oxygen-barrier material is laid flat in the designated area, ensuring sufficient coverage and close bonding with the surrounding soil. It is then fixed to the ground using mechanical fixing devices (such as nails and screws) to prevent displacement. Water is then injected into the oxygen-barrier material several times to allow the solid waste-based self-foaming carbon capture material to naturally foam and solidify inside the linear pile structure. The water injection interval is maintained at 3 hours per injection, with a total of 8 injections. For larger cracks, overlapping may be necessary to ensure the material forms a complete oxygen barrier, preventing oxygen penetration.
[0065] Next, the CO2 captured by the coal-fired power plant in the mining area is transported through boreholes or pipelines to the goaf area below the surface fissures. After sealing, the goaf and the surface can form a closed space to store the CO2. At the same time, the oxygen-barrier material can also absorb and block the CO2 that escapes from the goaf to the air leakage channel, thereby achieving multiple effects of pollution reduction and carbon reduction, and inertizing the environment for spontaneous combustion of coal in the goaf.
[0066] Finally, sensors are used to monitor parameters such as oxygen concentration, temperature, and pressure in the goaf area in real time to ensure the effectiveness of the oxygen barrier. The environmentally friendly oxygen barrier material is regularly inspected to assess its structural integrity and oxygen barrier effect; any defects are promptly addressed by replenishing or maintaining the material. If excessively high temperatures or oxygen concentrations are detected in the goaf, an emergency response procedure should be initiated immediately to ensure safety. The rapid-response capability of the oxygen barrier material should be utilized for further localized isolation to slow the rate of coal oxidation and temperature rise.
[0067] Evaluation of the effect and performance of oxygen barrier implementation in the fissures of Example 1:
[0068] Before testing the effectiveness of leak-sealing, oxygen-barrier, and fire-extinguishing measures in specific mining areas, the performance of the components of the environmentally friendly oxygen-barrier fire-extinguishing material was first characterized. The performance testing methods mainly included: determining the material's water permeability using a static water permeability test; conducting an abrasion test using a Martindale abrasion tester to obtain the material's abrasion resistance; determining its tensile strength using a tensile testing machine to ensure the material remains stable under load (it should not be less than 15 MPa); testing its tear resistance using a tear tester; analyzing its UV resistance after 200 hours of UV irradiation using an accelerated UV aging tester; and determining the material's temperature resistance within a temperature range of -20℃ to 60℃. The test results are shown in Table 1.
[0069] Table 1 Results of Material Performance Parameter Measurement
[0070]
[0071] Test results for the permeable and abrasion-resistant cover showed that the material's permeability was 1000 L / (m²). 2The surface material exhibits a tensile strength of 17 MPa, ensuring smooth water injection; a wear rate of 12% after 1000 abrasion cycles, guaranteeing its durability and extended service life; a tear strength of 45 N, ensuring good tear resistance and adaptability to underground conditions; an 8% wear rate, guaranteeing durability; and a tensile strength of approximately 85% of its original value after treatment at 70℃ for a certain period. After 200 hours of ultraviolet irradiation, the tensile strength decreased by 10%, indicating its adaptability to sunlight exposure. Furthermore, the tensile strength remains at approximately 92% of its original value after a certain period at temperatures ranging from -20℃ to 60℃. Therefore, this permeable and wear-resistant surface cover meets the application requirements for sealing air leaks in shallowly buried coal seams during the preparation of oxygen-barrier materials, demonstrating promising market prospects.
[0072] The waterproof sealing composite fabric's waterproofing capability under a 1m water column was determined using a water pressure test. Other test methods were referenced from those used for permeable and abrasion-resistant covers. The permeability results showed that this oxygen-barrier material could still prevent moisture-related problems in a sealed environment, with no leakage at the bottom. The tensile strength was 30MPa, ensuring stable use even under load. The tear strength reached 65N to prevent tearing due to external forces during use. The abrasion rate was 8%, ensuring the material's durability. After treatment at 70℃ for a certain period, its tensile strength remained at approximately 85% of its original value. Furthermore, after 200 hours of ultraviolet irradiation, the tensile strength decreased by 12%. Therefore, this waterproof sealing composite fabric fully meets the application requirements for sealing air and water leaks in shallow buried coal seams, effectively preventing air and water leakage in actual construction and ensuring the safety and stability of the coal seam.
[0073] For solid waste-based self-foaming carbon capture materials, the compressive strength, density, permeability, and gas leakage resistance were mainly measured. Specific testing methods included: testing the compressive strength using a universal testing machine; calculating the density by measuring the volume and mass of the sample; measuring the permeability using a permeability meter; and measuring the gas leakage rate under specific pressure and time conditions. The test results are shown in Table 2. The results show that the compressive strength of the solid waste-based self-foaming carbon capture material meets the requirements for load-bearing capacity and stability; its density meets the requirements for lightweight and good thermal insulation performance; its low permeability effectively prevents moisture penetration, making it suitable for use in humid environments; and the gas leakage rate is less than 0.1 L / min·m. 2 It can effectively prevent gas leakage.
[0074] Table 2 Performance Test Results of Solid Waste-Based Self-Fogging Carbon Capture Materials
[0075] Test Results 2.0MPa <![CDATA[700kg / m 3 ]]> <![CDATA[0.05L / (m 2 ·h)]]> <![CDATA[0.05L / min·m 2 ]]>
[0076] After the prefabricated oxygen-barrier material was cured by water injection, the performance parameters of commonly used foamed cementitious materials were compared, as shown in Table 3. The results showed that the environmentally friendly oxygen-barrier fire extinguishing material performed well in terms of compressive strength and impermeability, and its lower shrinkage rate made it more advantageous in terms of seepage prevention and sealing.
[0077] Table 3. Performance Test Results of Oxygen Barrier Materials and Foamed Cementitious Materials
[0078] oxygen barrier material 4.6MPa 3.5MPa 1×10^-9cm / s 0.05% Foamed cementitious materials 1.9MPa 1.5MPa 1×10^-8cm / s 0.2%
[0079] A certain mine consists of shallowly buried, closely spaced coal seams. The entire minefield is divided into five panels. During on-site assessment and exploration, a handheld GPS recorder was used to locate the fractures and record their coordinates. A compass was used to identify the direction of fracture extension, and a measuring tape was used to measure the width, depth, and spacing of the fractures. Tests revealed that the surface fractures in this mine are divided into collapse-type fractures and graben-type fractures. These two types of fractures are located on the surface between the two main roadways of the working face and directly above the goaf behind the working face, respectively. The fractures persist as the working face is continuously mined, promoting the spontaneous combustion of coal in the goaf. Therefore, it is necessary to take corresponding measures to prevent spontaneous combustion of coal in the goaf by addressing the air leakage caused by surface fractures in this mine.
[0080] Monitoring revealed that coal oxidation and heating were occurring in the goaf area directly beneath a surface fissure in a certain mining area, with a CO concentration reaching 250 ppm. This indicates a potential risk of spontaneous combustion of residual coal in this goaf area. To effectively prevent spontaneous combustion of coal in the goaf area of this shallowly buried coal seam, the mine adopted the preparation and application method of the environmentally friendly oxygen-barrier fire-extinguishing material based on CCS proposed in this invention, combined with the appendix of this invention. Figure 1 and Figure 2 The specific steps are as follows:
[0081] First, an on-site investigation and location of the surface fissures in the mine were conducted. A comprehensive survey of the area surrounding the coal mine was carried out to pinpoint the specific location and morphological characteristics of the surface fissures and assess their air leakage intensity. Simultaneously, oxygen-barrier materials were prepared. Oxygen-barrier materials were prefabricated according to the material ratios required by this invention, ensuring they meet engineering requirements and possess good compressive strength and water resistance, thus guaranteeing stability and durability in later applications.
[0082] Secondly, apply oxygen-barrier material to the surface fissures, ensuring the material fully covers the fissures. Use mechanical or manual methods to ensure good contact between the material and the ground, creating a good seal. After fixing, inject water into the oxygen-barrier material several times to allow the solid waste-based self-foaming carbon capture material to naturally foam and solidify inside the linear pile structure. The water injection interval should be maintained at 3 hours per injection, with a total of 9 injections. For larger fissures, overlapping may be necessary to ensure the material forms a complete oxygen barrier, preventing oxygen penetration.
[0083] Next, after the sealing is completed, CO2 is injected into the enclosed space to ensure that the CO2 is fully distributed within the goaf. The CO2 captured by the coal-fired power plant in the mining area is transported to the goaf area where the surface fissures are sealed through boreholes or pipelines. The sealed goaf can form a closed space to store the CO2. At the same time, the oxygen-barrier material can also absorb and block the CO2 escaping from the goaf into the air leakage channels. Thus, it achieves multiple effects such as solid waste utilization, CO2 mineralization and storage, and reduction of oxygen concentration in the goaf, thereby achieving the goals of pollution reduction, carbon reduction, and disaster mitigation through waste.
[0084] Finally, after construction is completed, the sealing effect of the cracks should be tested regularly, and a gas system should be established. Combined with the leak-sealing effect of the oxygen-barrier material, sensors should be used to monitor parameters such as oxygen concentration, CO concentration, and CO2 concentration in the goaf and the sealed area in real time to ensure the effectiveness of the sealing barrier. The environmentally friendly oxygen-barrier material should be inspected regularly to assess its structural integrity and oxygen-barrier effect; if defects are found, the material should be replenished or maintained promptly. If excessively high temperatures or oxygen concentrations are found in the goaf, to ensure safety, an emergency response procedure should be quickly activated, utilizing the rapid response capability of the high-toughness oxygen-barrier material for further local isolation to slow down the rate of coal oxidation and temperature rise.
[0085] In implementing the preparation and application method of the CCS-based environmentally friendly oxygen-barrier fire-extinguishing material of this invention in the mining area, corresponding monitoring is required for aspects such as the prevention and control of spontaneous combustion of coal in the goaf, the sealing of effective CO2 storage space, and the absorption of escaping CO2. To evaluate the sealing effect and related fire prevention and storage performance, oxygen and CO2 concentration data can be recorded periodically before and after sealing using oxygen and CO2 sensors for comparative analysis. The following are specific examples of the sensor layout, monitoring data, and their changes.
[0086] An oxygen sensor is installed above and below the goaf entrance of the sealing area to monitor changes in oxygen concentration before and after sealing. A CO sensor is installed at the return air corner of the working face to monitor changes in carbon monoxide concentration. CO2 sensors are installed at the edge of the oxygen barrier material (outer sealing area), below the oxygen barrier material, and at the CO2 injection port inside the goaf to monitor CO2 concentration within the goaf, ensuring monitoring of CO2 leakage and concentration changes within the sealing area. Data from the gas sensors before and after sealing are compared to analyze the trends in oxygen and CO2 concentrations, confirming the effectiveness of CO2 containment and whether there is a risk of spontaneous combustion in the goaf.
[0087] By monitoring the changes in the concentrations of oxygen, CO, and CO2, it was found that before the application of the technology of this invention, the oxygen volume concentration above the surface fissures was 21%, the oxygen concentration at the entrance of the goaf was 19%, the CO concentration at the return air corner of the working face was 260 ppm, the CO2 concentration at the edge of the oxygen barrier material (outer sealing area) and below the oxygen barrier material was approximately 0.04%, and the CO2 concentration inside the goaf was approximately 0.1%. This indicates that there is a certain risk of spontaneous combustion of coal in the goaf below the surface fissure area. After implementing the preparation and application method of the CCS-based environmentally friendly oxygen barrier fire prevention and extinguishing material of this invention for 72 hours, the oxygen volume concentration above the surface fissures was significantly reduced to 14%, the oxygen concentration at the entrance of the goaf was 12%, the CO2 concentration at the edge of the oxygen barrier material (outer sealing area) was approximately 0.04%, the CO2 concentration below the oxygen barrier material was approximately 1.5%, the CO concentration at the return air corner of the working face was 25 ppm, and the CO2 concentration inside the goaf was 2.5%. Furthermore, monitoring one week after implementing the fire prevention and extinguishing technology of the present invention revealed that the CO2 concentration in the enclosed space was 3% and tended to be stable.
[0088] In summary, the significant reduction in oxygen concentration indicates that the fire prevention and extinguishing technology of this invention effectively reduces the infiltration of outside air, lowers the oxidation risk in the goaf, and helps prevent spontaneous combustion of coal. The gradual decrease in CO concentration to 20 ppm indicates that the coal oxidation and heating process in the goaf was effectively controlled after sealing, reducing safety hazards. The changes in CO2 concentration at the edge of the oxygen-barrier material (outer sealing area) and inside the goaf demonstrate the effective sealing of injected CO2 within the enclosed space, indicating that the material can form an effective sealing space, further reducing oxygen concentration and thus reducing the risk of coal oxidation. Furthermore, the changes in CO2 concentration at the edge of the oxygen-barrier material (outer sealing area) and below the oxygen-barrier material demonstrate that during the implementation of the technology described in this invention, the solid waste-based self-foaming carbon capture material can effectively absorb and mineralize the leaked CO2 gas in the sealing space. This further illustrates the effectiveness of this invention in preventing spontaneous combustion of coal in the goaf caused by surface fissures in shallow-buried coal seams and in achieving CO2 sealing, providing a valid theoretical basis and practical reference for future coal seam safety management.
[0089] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely illustrative examples, and various changes or modifications can be made to these embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is defined only by the appended claims.
Claims
1. A method for preparing an environmentally friendly oxygen-barrier fire-extinguishing material based on CCS, characterized in that, Includes the following steps: Step 1), material prefabrication; ① Prefabricated permeable and wear-resistant cover A fabric is formed by blending spandex, polyester fiber and polypropylene fiber, and then polyurethane is coated on the surface of the fabric and cured to obtain a water-permeable and wear-resistant cover. ② Prefabricated waterproof and sealing composite fabric Glass fibers with a diameter of 9-13μm and aramid fibers with a diameter of 12-15μm are immersed in a polyurethane adhesive solution, then removed and dried and cured. The treated glass fibers and aramid fibers are laid on both sides of a Sympatex film with a thickness of 10-20μm, and then hot-pressed to obtain a waterproof and sealing composite fabric with a three-layer structure. ③ Prefabricated solid waste-based self-foaming carbon capture material Steel slag, blast furnace slag, fly ash, desulfurized gypsum, modified starch-based foaming agent, cocoamide, xanthan gum and water are mixed evenly to obtain solid waste-based self-foaming carbon capture material, wherein the modified starch-based foaming agent is obtained by combining corn starch and water glass; ④ Prefabricated mesh support Loofah sponges are broken into 1-5cm segments and soaked in a mixed aqueous solution of chlorovinylidene ester emulsion and VAE emulsion to modify the loofah sponges and obtain modified loofah sponge fibers. Then, the temperature of the hot press is controlled at 100-150℃ and a pressure of 1-5MPa is applied for hot pressing to melt-bond the thermoplastic polyurethane material with the modified loofah sponge fibers and polypropylene fibers or polyester fibers to form a multilayer structure and obtain a mesh scaffold. Step 2), composite assembly of prefabricated materials; First, a waterproof and sealing composite fabric is laid as the bottom surface. The mesh support is then evenly spaced on the waterproof and sealing composite fabric and fixed with adhesive. Next, solid waste-based self-foaming carbon capture material is filled into the frame formed by the mesh support, so that it is evenly filled into the entire space of the mesh support. Finally, a water-permeable and wear-resistant cover is laid as the top surface and fixed to the mesh support with adhesive, thus obtaining an environmentally friendly oxygen-barrier fire-extinguishing material based on CCS.
2. The preparation method of the environmentally friendly oxygen-barrier fire-extinguishing material based on CCS according to claim 1, characterized in that, The raw materials of the permeable and wear-resistant cover are: textile waste spandex accounting for 10-15 wt%, polyester fiber accounting for 40-55 wt%, and polypropylene fiber accounting for 30-50 wt%; the amount of polyurethane coating accounts for 10-14% of the total fiber mass.
3. The preparation method of the environmentally friendly oxygen-barrier fire-extinguishing material based on CCS according to claim 1, characterized in that, The waterproof and sealing composite fabric uses aramid fiber accounting for 45-55% of the mass and glass fiber accounting for 55%-45% of the mass.
4. The preparation method of the environmentally friendly oxygen-barrier fire-extinguishing material based on CCS according to claim 1, characterized in that, The raw material components of the solid waste-based self-foaming carbon capture material are formulated according to the following weight: 30-40 parts steel slag, 25-35 parts blast furnace slag, 15-25 parts fly ash, and 5-10 parts desulfurized gypsum; the modified starch-based foaming agent and coconut oil amide account for 3%-5% of the total mass of the solid waste-based self-foaming carbon capture material; the mass ratio of the modified starch-based foaming agent to coconut oil amide is 4:1, and the modified starch-based foaming agent is obtained by compounding corn starch and water glass at a mass ratio of 1:0.3; the amount of xanthan gum is 0.1%-0.3% of the total mass of the modified starch-based foaming agent and coconut oil amide; and the water-to-solid ratio is 0.4-0.
5.
5. The preparation method of the environmentally friendly oxygen-barrier fire-extinguishing material based on CCS according to claim 1, characterized in that, When prefabricating waterproof and sealing composite fabrics, the hot pressing process is as follows: hot pressing is performed for 5-10 minutes at 120-150℃ and 10-15MPa using a hot pressing device.
6. An environmentally friendly oxygen-barrier fire-extinguishing material based on CCS, characterized in that, It is prepared by the method described in any one of claims 1-5.
7. The application of the CCS-based environmentally friendly oxygen-barrier fire-extinguishing material as described in claim 6 for the prevention and control of spontaneous combustion of coal in goaf areas of shallow-buried coal seams, characterized in that... The environmentally friendly oxygen-barrier fire extinguishing material is unfolded and completely covers the surface fissures of the shallow buried coal seam. Then, water is injected into the environmentally friendly oxygen-barrier fire extinguishing material so that the solid waste-based self-foaming carbon capture material can naturally foam and solidify inside the mesh support structure.
8. The application according to claim 7, characterized in that, The interval between water injections should be 2-3 hours, and the number of water injections should be 8-10 times.
9. The application according to claim 7, characterized in that, The environmentally friendly oxygen-barrier fire-fighting material is unfolded and completely covered to cover the surface fissures of the shallow buried coal seam. The environmentally friendly oxygen-barrier fire-fighting material is then fixed to the ground using a mechanical fixing device, which may be a nail, screw, or anchor bolt.
Citation Information
Patent Citations
Fire preventing and extinguishing type air leaking isolation material of mined-out area and construction method
CN104763460A
Leaking stoppage and fire prevention and extinguishing material for underground coal mine isolation coal pillar and use method thereof
CN117734265A